Technical Change and Firm Size: The Pharmaceutical Industry - Vernon, John M.; Gusen, Peter (The Review of Economics and Statistics, 1974)
FISHER and TEMIN (1973) have argued recently that many empirical studies1 re-lating to the Schumpeterian hypothesis are in-appropriate for testing that hypothesis. They